1991
DOI: 10.1002/1097-0142(19910201)67:3<557::aid-cncr2820670304>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and pituitary gonadotropin values and responses to acute luteinizing hormone-releasing hormone (LHRH) challenge in patients having long-term treatment with a depot lhrh analogue

Abstract: Sixty patients with advanced prostatic carcinoma were treated with monthly subcutaneous injections of a depot formulation of goserelin, a luteinizing hormone-releasing hormone (LHRH) analogue (Zoladex, ICI Pharma, Destelbergen, Belgium). All patients were regularly evaluated with measurements of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone (T), and prolactin (PRL) levels. In 15 patients among them who could be treated for more than 42 months, an LHRH stimulation test was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…FSH receptor expression is increased in prostate cancer compared with benign prostatic epithelium. Exogenous FSH stimulates proliferation and decreases apoptosis in androgen-independent cells in vitro [81]. These observations raise the possibility that FSH and its receptor may participate in hormone-refractory prostate cancer growth regulation.…”
Section: New Research Developmentsmentioning
confidence: 82%
See 1 more Smart Citation
“…FSH receptor expression is increased in prostate cancer compared with benign prostatic epithelium. Exogenous FSH stimulates proliferation and decreases apoptosis in androgen-independent cells in vitro [81]. These observations raise the possibility that FSH and its receptor may participate in hormone-refractory prostate cancer growth regulation.…”
Section: New Research Developmentsmentioning
confidence: 82%
“…The discovery of the GnRH-II isoform raised the question as to whether this isoform is likely to have a diverse functional activity than GnRH-I. In human endometrial and ovarian cancer cells, GnRH-II seems to be a more potent inhibitor of cell proliferation compared with GnRH-I [81]. Lately, it was noticed that GnRH-II produced by human T cells, activates laminin receptor gene expression and cell migration [77].…”
Section: New Research Developmentsmentioning
confidence: 99%
“…Studies have demonstrated direct action of GnRH-I on prostate cancer cells. GnRH-I agonists induce a direct inhibitory action on EGF or IGF-induced prostate cancer cell proliferation [38]. The discovery of the GnRH-II isoform raised the question as to whether this isoform is likely to have a diverse functional activity than GnRH-I in prostate cancer cells.…”
Section: B Gnrh Antagonist Therapymentioning
confidence: 99%
“…During continued administration, serum levels of these gonadotrophins are suppressed, with LH levels declining to about 1 to 2 1U1L[2.3] (normal values 3 to 25 lUlL) and those of FSH to a nadir value of about 3 to 4 IUIL[2.3] (normal values 2 to 15 lUlL). The extent of the decrease in LH levels (50 to 80%) was consistently greater than that in FSH levels (about 30 to 50%), [2][3][4] and was maximal after 1 or 2 subcutaneous administrations of goserelin 3.6mg as a depot preparation,l2] Serum levels of FSH were reported to remain close to nadir values during long term goserelin treatment in some studies, [3.5] but Mahler et al [2] reported that after reaching a nadir on day 35 of treatment, FSH levels gradually increased. In contrast, Petersson et aI.l6] noted that although serum levels of LH and FSH declined during 3 to 6 months' treatment with goserelin, the decrease was not significant and levels remained within normal limits.…”
Section: Effects On Gonadotrophinsmentioning
confidence: 99%
“…[2] Plasma gonadotrophin levels were increased 9 and 10 months after goserelin withdrawal compared with values observed at the end of 13 and 26 months' treatment in 2 men with prostate cancer,l3]…”
Section: Effects On Gonadotrophinsmentioning
confidence: 99%